Well-Posedness and Stability Result of the Nonlinear Thermodiffusion Full von Kármán Beam with Thermal Effect and Time-Varying Delay. (5th April 2021) - Choucha, Abdelbaki; Ouchenane, Djamel; Boulaaras, Salah Mahmoud; Cherif, Bahri Belkacem; Abdalla, Mohamed
Abstract : In this work, we consider a new full von Kármán beam model with thermal and mass diffusion effects according to the Gurtin-Pinkin model combined with time-varying delay. Heat and mass exchange with the environment during thermodiffusion in the von Kármán beam. We establish the well-posedness and the exponential stability of the system by the energy method under suitable conditions.